2020
DOI: 10.1021/acs.jpca.0c02132
|View full text |Cite
|
Sign up to set email alerts
|

Direct Trace Fitting of Experimental Data Using the Master Equation: Testing Theory and Experiments on the OH + C2H4 Reaction

Abstract: The supplementary information (369 pages) contains: Pages S2 -S6 Fits to all 96 traces showing the raw data and final fit. At the top of each trace are the associated experimental conditions. Pages S7 -S99 An example MESMER input file for the analysis. The majority of the information, from page S12 onwards, are the experimental input data for each trace. Pages S100 -S369 The associated MESMER log file. The data from page S104 onwards are the experimental data and associated fit. S2 Trace FitsPlots of the trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
(95 reference statements)
2
22
0
Order By: Relevance
“…Finally, rate constants associated to transition states (adiabatic reactions) as well as intersystem crossings (nonadiabatic reactions) have been determined with the program MESMER version 5.2. [58][59][60][61][62] Microcanonical rate constants of transitions states have been computed with the Rice and Ramsperger-Kassel-Marcus (RRKM) theory [63][64][65][66] and the microcanonical rate coefficients of ISCs have been calculated with the Landau-Zener 67,68 model with inclusion of tunnelling corrections as described by Harvey and Aschi. 69…”
Section: E [Ev]mentioning
confidence: 99%
“…Finally, rate constants associated to transition states (adiabatic reactions) as well as intersystem crossings (nonadiabatic reactions) have been determined with the program MESMER version 5.2. [58][59][60][61][62] Microcanonical rate constants of transitions states have been computed with the Rice and Ramsperger-Kassel-Marcus (RRKM) theory [63][64][65][66] and the microcanonical rate coefficients of ISCs have been calculated with the Landau-Zener 67,68 model with inclusion of tunnelling corrections as described by Harvey and Aschi. 69…”
Section: E [Ev]mentioning
confidence: 99%
“…Simulations using the full potential energy surfaces described by Yuan et al and those with the minor modifications indicated that such modifications reduce the computational cost of the fits, without any significant loss in accuracy. Collisional energy transfer was modelled using <ΔE>down = 250 × (T/298) 0.25 cm -1 for N2, 29,[41][42][43] 180 × (T/298) 0.5 cm -1 for Ar, 41,43 and 125 cm -1 × (T/298) 1.0 for He. 41,43 The initial reaction between OH and the furan occurs on barrierless surfaces to form pre-reaction complexes (see Figures 5 and S1).…”
Section: Master Equation Calculationsmentioning
confidence: 99%
“…As mentioned in the Introduction, in some cases it is advantageous to directly use experimental traces for parameter optimization. The particulars of the trace fitting feature in MESMER are explained in ref (3). Briefly, the error function that is minimized is…”
Section: Master Equation Modelingmentioning
confidence: 99%
“…This issue has been addressed by Medeiros et al using a least squares fit of the amplitude of the calculated trace to the measured trace. The details are presented in ref (3).…”
Section: Master Equation Modelingmentioning
confidence: 99%
See 1 more Smart Citation